2010
DOI: 10.1016/j.socscimed.2010.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with partner referral among patients with sexually transmitted infections in Bangladesh

Abstract: Understanding the demographic, behavioural and psychosocial factors associated with partner referral for patients with sexually transmitted infections (STIs) is important for designing appropriate intervention strategies. A survey was conducted among STI clients in three government and three non-governmental organization-operated clinics in Dhaka and Chittagong city in Bangladesh. Demographic and psychosocial information was collected using a questionnaire guided by the Attitude-Social Influence-Self Efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
(33 reference statements)
1
9
0
Order By: Relevance
“…In our study, married participants were more willing to notify their partner than those with other marital status, which was consistent with the results of two other studies [27,28]. It is suggested that interdependency may be a motivation for married individuals to have a higher concern for their spouse's health [27], which leads to higher willingness to participate in PN. Our study also found that participants who had lived in Shenzhen longer and who had higher education were more willing to notify their partner about CT infections.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, married participants were more willing to notify their partner than those with other marital status, which was consistent with the results of two other studies [27,28]. It is suggested that interdependency may be a motivation for married individuals to have a higher concern for their spouse's health [27], which leads to higher willingness to participate in PN. Our study also found that participants who had lived in Shenzhen longer and who had higher education were more willing to notify their partner about CT infections.…”
Section: Discussionsupporting
confidence: 91%
“…Our study was based on the ASE model to explore factors associated with intention to screen for cervical cancer. The ASE model has previously been used for studies on uptake of voluntary counselling and testing for HIV [ 18 ] and partner referral to screen for sexually transmitted infections [ 32 ]. Inconsistent with the ASE model utilized in this study, some of the demographic characteristics of the respondents were associated with intention to screen for cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of individual behavior, issues of self-efficacy and empowerment have been shown to influence notification behaviors (15–18). Within dyadic partnerships, factors influencing PN include partnership type (primary/stable versus secondary/casual partner) and interpersonal dynamics (communication styles and relations of power within the partnership) (19–23).…”
Section: Introductionmentioning
confidence: 99%